Signaling through the nicotinic acetylcholine receptor in the liver protects against the development of metabolic dysfunction-associated steatohepatitis. - Heejin Jun; Shanshan Liu; Alexander J Knights; Kezhou Zhu; Yingxu Ma; Jianke Gong; Ashley E Lenhart; Xiaoling Peng; Yunying Huang; Jared P Ginder; Christopher H Downie; Erika Thalia Ramos; et al. (PLoS Biology)
Metabolic dysfunction-associated steatohepatitis (MASH) is the progressive form of liver steatosis, the most common liver disease, and substantially increases the mortality rate. However, limited therapies are currently available to prevent MASH development. Identifying potential pharmacological treatments for the condition has been hampered by its heterogeneous and complex nature. Here, we identified a hepatic nonneuronal cholinergic signaling pathway required for metabolic adaptation to caloric overload. We found that cholinergic receptor nicotinic alpha 2 subunit (CHRNA2) is highly expressed in hepatocytes of mice and humans. Further, CHRNA2 is activated by a subpopulation of local acetylcholine-producing macrophages during MASH development. The activation of CHRNA2 coordinates defensive programs against a broad spectrum of MASH-related pathogenesis, including steatosis, inflammation, and fibrosis. Hepatocyte-specific loss of CHRNA2 signaling accelerates the disease onset in different MASH mouse models. Activation of this pathway via pharmacological inhibition of acetylcholine degradation protects against MASH development. Our study uncovers a hepatic nicotinic cholinergic receptor pathway that constitutes a cell-autonomous self-defense route against prolonged metabolic stress and holds therapeutic potential for combatting human MASH.